Severe intellectual disability, West syndrome, Dandy–Walker malformation, and syndactyly in a patient with partial tetrasomy 17q25.3. Issue 12 (16th August 2013) - Hackmann, Karl; Stadler, Anja; Schallner, Jens; Franke, Kathlen; Gerlach, Eva‐Maria; Schrock, Evelin; Rump, Andreas; Fauth, Christine; Tinschert, Sigrid; Oexle, Konrad
Abstract: We report on a de novo 0.5 Mb triplication (partial tetrasomy) of chromosome 17q25.3 in a 10‐year‐old girl with severe intellectual disability, infantile seizures (West syndrome), moderate hearing loss, Dandy–Walker malformation, microcephaly, craniofacial dysmorphism, striking cutaneous syndactyly (hands 3–4, feet 2–3), joint laxity, and short stature. The triplication resulted from the unusual combination of a terminal duplication at 17qter and a cryptic translocation of an extra copy of the same segment onto chromosome 10qter. The breakpoint at 17q25.3 was located within the FOXK2 gene. SNP chip analysis suggested that the rearrangement occurred during paternal meiosis involving both paternal chromosomes 17. © 2013 Wiley Periodicals, Inc.